Language : its structure and use - Finegan, Edward (Unites States of America : Wadsworth, Cengage Learning, 2012)
For century upon century, philosophers, rhetoricians and grammarian have analyzed the uses to which people put language in their everyday lives and the linguistics structures and social structures supporting that use.
Part1. Language Structure -- Part2. Language Use -- Part3. Language Change, Language Development and Language Acquisition .
Includes bibliographical references and index.
Keywords: LANGUAGE